Improving gluten-free bread volume using additives: A review - William Asongni Djeukeu; Julien Armel Agamou Assiene; Fabrice Fabien Dongmo Dongho; Vanessa Guemkam Boudjeka; Adelaide Mawamba Demasse; Fernande Christine Biyegue Nyangono; Evariste Fedoung Fongzossie; Inocent Gouado (Food Chemistry Advances)
The use of additives in gluten-free bread for characteristics improvement has led to a wide range of formulations. Moreover, the choice of additives seems arbitrary and hinders standardization of products. This review evaluates additives combination strategies to enhance the volume of gluten-free breads, based on data from 42 published papers. The literature was sourced from databases such as Google Scholar, Scopus, ScienceDirect, and Researchgate using “gluten-free bread”, “improvement”, and “additives” as keywords. Information on the additives used, main ingredient, other ingredient composition, increase in bread volume, and other ingredient contributions to the formulation was collected. The main ingredients used in gluten-free bread development were plotted on a bar graph. The contribution of other ingredients in the formulation and the percentage increase in bread volume were also calculated. The formulations strategies are typically structured as a major ingredient (usually a carbohydrate source) + additive + other ingredients. The major ingredient, often a starch or starch-rich matrix, forms the basic structure of the bread. Additives such as proteins, enzymes, fibers, and hydrocolloids are generally used with other ingredients such as fat sources, sweetener, protein, and fiber. The findings provide the overall strategy behind the increase of the volume of gluten-free breads.